The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.37358/mp.18.2.5002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dental Bleaching on Marginal Sealing of Composite Resin Restorations Bonded with a Universal Adhesive

Abstract: The aim of this study was to evaluate the postoperative effect of one bleaching agent containing 40% peroxide hydrogen on the interface between dental tissues and a microhybrid composite resin bonded with a universal adhesive applied in total-etch and self-etch technique. Standardized Class V restorations were performed in oral surfaces of 40 extracted human molars with the gingival margins placed bellow the cement-enamel junction. For 20 restorations the adhesive was applied with preliminary etching and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The surface of rebuilt crystals is made of a facet of well-structured minerals; it is more resistant and less soluble to acid than the original mineral that contained a carbon apatite; the subsequent acid attacks will be less efficient [22]. The qualities necessary for an ideal remineralization agent are the following: (1) to release calcium and (3) not to favour the formation of plaque; (4) to be active at an acid pH acid in order to stop demineralization during the cariogenic attack; (5) to be active in the xerostomic patients, for whom saliva is not efficient in blocking the caries process; (6) to encourage remineralizing properties of saliva; (7) the new materials must present additional advantages compared to fluoride [23,24]. During the time manufacturers tried to improve toothpastes content by adding different beneficial agents, except fluoride.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface of rebuilt crystals is made of a facet of well-structured minerals; it is more resistant and less soluble to acid than the original mineral that contained a carbon apatite; the subsequent acid attacks will be less efficient [22]. The qualities necessary for an ideal remineralization agent are the following: (1) to release calcium and (3) not to favour the formation of plaque; (4) to be active at an acid pH acid in order to stop demineralization during the cariogenic attack; (5) to be active in the xerostomic patients, for whom saliva is not efficient in blocking the caries process; (6) to encourage remineralizing properties of saliva; (7) the new materials must present additional advantages compared to fluoride [23,24]. During the time manufacturers tried to improve toothpastes content by adding different beneficial agents, except fluoride.…”
Section: Resultsmentioning
confidence: 99%
“…In oral environment the teeth and the materials for restoration are exposed to diverse acidic or mechanical challenges that lead to dental hard tissues demineralization [1] or wear [2], to material degradation [3,4] and to material-tooth interface failure [5][6][7].…”
mentioning
confidence: 99%
“…Modern adhesive resins for restorative therapy can form strong bonds of 30–50 MPa with dentin, but for a limited time [ 2 ]. The limited durability of this bond affects the restoration’s longevity [ 3 ]. Previous studies have shown that 75% of resin restorations fail as a result of the degradation of the interface between the adhesive resin and dentin, resulting in restoration loss, secondary caries or pulpal sensitivity [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“… 6 However, some other studies that used a universal adhesive in both self-etch and total-etch methods concluded that etching and bleaching with 40% hydrogen peroxide does not affect the microleakage of enamel and dentin margins. 7 Therefore, considering the contradictions in the past studies and the lack of sufficient information regarding the effect of bleaching on the microleakage of universal adhesives, the present study investigated the effects of home bleaching and office bleaching on the microleakage of class five composite resin restorations using two universal adhesive systems.…”
Section: Introductionmentioning
confidence: 99%